The effect of profitability and executive characteristics on corporate tax avoidance - Pristyanti, Novina Anggi; Harared, Bunga Anisah (Educoretax, 2026)
Tax avoidance practices are a crucial issue in tax accounting because they directly affect state revenue and reflect a company's strategy for legally managing its tax obligations. High profitability and executive decision-making characteristics influence a company's propensity to engage in tax avoidance, particularly in the property, real estate, and building construction sectors, which have relatively complex asset characteristics and funding structures. This study aims to analyze the effect of profitability and executive characteristics on tax avoidance in property, real estate, and building construction companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Profitability is proxied by Return on Assets (ROA), while executive characteristics are proxied by risk-taking, reflecting management's tendency to take on risk. Data were obtained from the company's annual financial statements using purposive sampling based on specific criteria. The analytical method used was panel data regression with a random-effects model. The results show that profitability has a positive and significant effect on tax avoidance, indicating that companies with higher profit levels tend to engage in more aggressive tax planning. In addition, risk-taking executive characteristics also have a positive and significant effect on tax avoidance. The implications of this research are expected to enrich the tax accounting literature and to be considered by regulators and management in improving corporate tax supervision and governance.